2018
DOI: 10.1002/bjs.10956
|View full text |Cite
|
Sign up to set email alerts
|

CCR-CARESS score for predicting operative mortality in patients with colorectal cancer

Abstract: Elderly patients with co-morbidity and palliative intention of surgery have an unacceptably high risk of death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Some of them, such as age, ASA score and pulmonary comorbidity, have already been reported as being associated. Advanced age is a well‐known risk factor for postoperative death in colorectal surgery . In our study, the postoperative mortality rate increased by approximately 5% for every 5 years starting at 65.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Some of them, such as age, ASA score and pulmonary comorbidity, have already been reported as being associated. Advanced age is a well‐known risk factor for postoperative death in colorectal surgery . In our study, the postoperative mortality rate increased by approximately 5% for every 5 years starting at 65.…”
Section: Discussionmentioning
confidence: 49%
“…Surgery for OCC is associated with worse short-term outcomes in comparison with elective surgery, with postoperative mortality and morbidity rates of 8%-15% and 40%, respectively [4][5][6][7]. Several studies have reported risk factors or developed scoring systems to predict postoperative mortality after colorectal surgery [the Association Franc ßaise de Chirurgie (AFC) score, the Colorectal-Physiological and Operative Severity Score for Enumeration of Mortality and Morbidity score, the Association of Coloproctology of Great Britain and Ireland score, the Cleveland Clinic Foundation CRC model, the Identification of Risk in Colorectal Surgery model and the CCR-CARESS score] [8][9][10][11][12][13][14][15]. Most of them found that emergency surgery was an independent factor for postoperative mortality [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, patients ≥70 years old are twice as likely to die during the index hospitalization. [9,11] A critical aspect of postoperative recovery for older patients is maintaining cognitive function and avoiding delirium. Patients who develop delirium face a twofold increased risk of death, a 2.4-fold greater risk of institutionalization, and a 12-fold increase in the risk of developing dementia after hospital discharge.…”
Section: Perioperative Complications In the Older Patientsmentioning
confidence: 99%
“…Multiple trials have evaluated the possible risk factors or created prognostic scores for mortality after colorectal surgery, and emergency surgery was found to be a strong predictor for post-operative mortality (14)(15)(16). Nonetheless, these studies included patients with elective and emergency colorectal cancer patients.…”
Section: Introduction Introductionmentioning
confidence: 99%